Effect of the Board of Directors on Firm Performance (2017)
This paper aims to study the relationship between three characteristics of the Board of Directors (Board Size, Independent Members, and Number of Meetings) and performance (ROA, ROE) in Colombian firms during the 2008-2014 period. The analysis was performed using regression models in a balanced data panel that considered random effects. The results show that BD optimal size for the Colombian case is between 6 and 10 members; and there is no evidence to affirm that the relationship between the characteristics of the studied BD and economic performance is significant.